The study of sound pollution in the educational area around Jalan Raja Laut, Kuala Lumpur / Fariza Shahkina Shahbuddin - Shahbuddin, Fariza Shahkina (Faculty Architecture, Planninng and Surveying, 2015)
Noise pollution is the disturbance or unwanted noise that may harm the enjoyable and balance of human or animal life. Machines, transportation systems and poor urban planning is the source of most outdoor noise worldwide that may give rise to noise pollution. High sound levels can contribute to effects in humans joy, increased blood pressure, and an increase in stress and an increased incidence of coronary artery disease. In animals, noise can increase the risk of death by altering predator or prey detection, interfere with reproduction and navigation, and contribute to permanent hearing loss. The problem statement Review annoyance caused by noise heard in schools by Dockrell, 2001, suggests that certain sound like overflying planes, trains or sirens can affect children and teachers disproportionate to their contribution to the overall sound of the school environment.Most of the schools that are in the vicinity of Jalan Raja Laut, there is SK Pendidikan Khas (Cacat Penglihatan) Jalan Batu, SK (L) Jalan Batu and SK (P) Jalan Batu that have been contaminated with a variety of noise such as motor vehicles and public transport. Thus, the study should be conducted to determine the level of noise that interfere with students in the schools involved. The aims of this study are to investigate the level and the effects of noise pollution in the vicinity of the schools also the sources of noise. The objective of this research are to measure the level of noise at the school area near to the main road, to identify the classification of vehicles contribute noise at the schools and to analyze and compare the sound level of the selected schools. Noise levels were monitoring at various location at Jalan Raja Laut during November,2014 (Wednesday- Friday). The data obtained was used to compute various noise parameters, namely equivalent continuous level (Leq), loudest period, exposure period and noise level (Ln). The data of noise levels taken at various location of the educational area of Jalan Raja Laut, Kuala Lumpur will be compared and analysed. Traffic volume count and noise indexes data were collected at three selected school around Jalan Raja Laut, there is SK Pendidikan Khas (Cacat Penglihatan) Jalan Batu, SK (Lelaki) Jalan Batu dan SK (Perempuan) Jalan Batu. The noise level that has been collected will be compared with the standards set by the Department of Environment (DOE) to determine the proper noise level at the school areas.